Facile preparation of sulfhydryl modified montmorillonite nanosheets hydrogel and its enhancement for Pb(II) adsorption. (October 2021) - Miao, Yiheng; Peng, Weijun; Cao, Yijun; Chang, Luping; Fan, Guixia; Yu, Futao
Abstract: In the work, sulfhydryl functionalized montmorillonite nanosheets based hydrogel balls were firstly synthesized for Pb(II) adsorption, and then characterized by scanning electron microscope (SEM), fourier transform infrared spectroscopy (FTIR), surface area analyzer (BET), thermogravimetry (TG), and zeta potential. Effects of initial solution pH, adsorbent dosage, contact time, temperature on Pb(II) adsorption of the resulting hydrogel balls were investigated systematically. The experimental results showed that the increase amount of sulfhydryl functionalized montmorillonite nanosheets (MMTNs-SH) maintained the hydrogel balls a better porous structure and bigger specific surface area, endowing it a bigger adsorption capacity. The adsorption process was fitted well with pseudo-second-order kinetics model and Freundlich model, and more than 97% of Pb(II) could be removed under the optimum conditions. Moreover, hydrogel spheres have a certain cycle performance. In addition, the interactions between Pb(Ⅱ) ions and the oxygen atoms in the hydroxyl groups and the sulfur atoms in the sulfhydryl groups, and the ion exchange in MMTNs-SH dominated the adsorption. Graphical abstract: Image 1 Highlights: MMNTs were successfully modified by sulfhydryl via a facile method. The resulting MMTNs-SH was used to prepare the MMTNs-SH based hydrogel balls. The hydrogel balls showed a greater adsorption capacity and better cycle property. The MMTNs-SH based hydrogel balls would be a promising adsorbent.